2020
DOI: 10.21272/fmir.4(1).109-116.2020
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance and Financial Reporting Quality: Preliminary Evidence from Saudi Arabia

Abstract: The investment climate in the country depends largely on the level of confidence of potential investors, which actualizes the need to provide transparent and quality financial reporting to economic entities. Powerful corporations that have established an effective corporate governance mechanism are able to provide high competitive advantage over the long term, contributing to their financial and economic stability. The purpose of the article is to determine the impact of corporate governance mechanisms on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
1
4
0
1
Order By: Relevance
“…These results also align with Franczak’s (2019) findings and Al-Khonain and Al-Adeem (2020), which indicate that corporate governance has a significant relationship with financial reporting transparency. This is because the transparency of financial reporting of companies whose shares are of interest to investors who are active in the financial market is one of the main elements of the contemporary economy.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…These results also align with Franczak’s (2019) findings and Al-Khonain and Al-Adeem (2020), which indicate that corporate governance has a significant relationship with financial reporting transparency. This is because the transparency of financial reporting of companies whose shares are of interest to investors who are active in the financial market is one of the main elements of the contemporary economy.…”
Section: Discussionsupporting
confidence: 85%
“…Ahmed and Hamdan (2015) also stated that good corporate governance increases investors’ confidence in financial reporting. Al-Khonain and Al-Adeem (2020) showed that corporate governance improves financial reporting quality. Research has also examined the effect of corporate governance characteristics on financial reporting transparency.…”
Section: Theoretical Issues and Hypotheses Developmentmentioning
confidence: 99%
“…The authors consider the main aspects of corporate social responsibility evolution in the context of implementing environmental management at industrial enterprises (Chigrin et al, 2011). Scholars are also actively investigating the impact of corporate social responsibility on the financial performance of businesses (Al-Khonain et al, 2020;Fadyeyeva, 2019;Khadidja et al, 2021;Tommaso, et al, 2019;Cyfert et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Так, вони розглядають основні аспекти розвитку корпоративної соціальної відповідальності в контексті впровадження екологічного управління на промислових підприємствах [27,33]. Також активно досліджено питання впливу корпоративної соціальної відповідальності на фінансові показники компаній [2,10,13,21].…”
Section: корпоративна соціальна відповідальність в управлінні трудови...unclassified